A phenomenological investigation of the beginning therapist's experience of the first session of psychotherapy with the first patient - Allen, Jennifer Ann (Rhodes University, Faculty of Humanities, Department of Psychology, 1987)
The aim of this project is to come to an understanding of how the situation of the first session of psychotherapy with the first patient is lived by the beginning therapist and what meaning this situation holds for him. The writer's interest in this phenomenon grew out of her own experience of this situation as a clinical Masters coursework student, an experience which was of important to the writer and meaningful still as a therapist in training. In dialogue with experienced therapists the importance of this situation was again made apparant. It was the opinion of these therapists that although for some the details of this experience had become dulled by time, what remained meaningful to them was that this experience was seen as the beginning of a project which remains important to them - they identified this situation as an important moment in the history of their development as psychotherapists. In the hope that the literature pertaining to psychotherapy would throw some light on this situation, the writer turned to a number of sources in this area to discover that no literature available to her elucidated this situation in a holistic manner. This led the writer to go back to the beginning therapists themselves so that they may speak for themselves of their experience of this situation. A phenomenological method of enquiry is implemented in this study as it renders the subject matter accessible to investigation, and allows it to reveal itself as it essentially is. This project is then an attempt to come to a general description of the beginning therapist's experience of the first session of psychotherapy with the first patient and thus to articulate the structure of the beginning therapist's lived situation (world) in this context.
Keywords: Psychotherapy; Feedback (Psychology); Psychotherapist and patient